Analisis Pembinaan Prestasi Atlet Bola Voli Putri Klub Anak Mandeh Kota Solok - Susilo Putra Alisman; Windo Wiria Dinata; Anggun Permata Sari (JURNAL STAMINA, 2022)
The problem in this research is how the implementation of volleyball sports coaching in the kids club Mandeh Kota Solok. The purpose of this study was: to determine the implementation of the pattern of volleyball coaching at the Mandeh Children's Club, Solok City. The conclusions from the research and discussion are: the pattern of fostering the achievement of volleyball athletes in the children's club, Solok City is running well, has been programmed, tiered and sustainable. The location of data collection at the children's volleyball club is stagnant. Methods of data collection using questionnaires, observation, documentation, and interviews. Sources of research data were 1 coach, 2 coaches, and 13 athletes. The result of research on the development of youth volleyball clubs in Solok City is the implementation of a coaching pattern directed at a training process in accordance with the needs of increasing athlete achievement. This is evidenced by the existence of a variety of training programs made by coaches so that athletes do not feel bored. Structured organizational structures, facilities and infrastructure can help athletes achieve maximum performance, although they still need improvement, more maximum funding, and increasing achievement.